Poslovna informatika - znanja za managerje - Grad, Janez (Uporabna informatika (Ljubljana), 2000)
In the paper we discuss the problem and curriculum paradigm of the informaticsthat should be a part of the various teaching programs within the faculties and graduate schools of economics and business in Slovenia, both at undergraduate and graduate level, embracing the general basic programs in business informatics, as well. The (business) informatics curriculum and the way of its presentation to the students should refelct and be based upon the latest achievements in information technology (IT), its usage in business processes, and its impacts on organizations, performance and results of business systems and processes. The graduates in business administration, economics and information management will in this way acquire the necessary knowlwdge for an efficient and successful usage of IT, enabling them to gain adequate strategic advantage in the fast growing business globalization.
Keywords: informacijska tehnologija; informacijski sistemi; poslovna informatika; uporabniške rešitve